RESPONSIVITAS PEGAWAI TERHADAP PELAYANAN E-KTP DI KABUPATEN ENREKANG - Ramadhan, Muhammad; Malik, Ihyani; Taufik, Ahmad (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
The aim of the study was to determine the Responsiveness of State Civil Apparatus in the E-KTP Service at the Office of the Population and Civil Registration Office of Enrekang Regency. This type of research uses a qualitative method with a type of research. Data collection techniques using the method of observation, interviews and documentation. Data analysis using an interactive analysis model. The results of the study show that the responsiveness of state civil servants in e-KTP services at the Population and Civil Registration Office of Enrekang Regency has not been maximized because there are several aspects, such as: the aspect of service speed and the ability to respond to complaints is still not optimal because there are still complaints from the community concerned rather than that aspect. However, in terms of the accuracy of the service, it has been said that this is the maximum, seen from the absence of public complaints regarding the accuracy of the aspect of the accuracy of the service.